Rebalancing the assembly lines: exact solution approaches - Sanci, Ece; Azizoglu, Meral (International journal of production research, 2017)
In this study, we consider an assembly line rebalancing problem with disruptions caused by workstation breakdowns or shutdowns. After the disruption, we aim to find a rebalance so as to catch the trade-off between the efficiency measure of cycle time and stability measure of number of tasks assigned to different workstations in the original and new balances. Our aim is to generate all nondominated objective vectors with respect to the efficiency and stability measures. We develop two optimisation algorithms: a Mixed Integer Linear Programming-based algorithm and a Branch and Bound algorithm. The results of our experiments have shown the favourable performances of both algorithms and the superiority of the Branch and Bound algorithm.